A stapled BIM peptide overcomes apoptotic resistance in hematologic cancers - James L. LaBelle; Samuel G. Katz; Gregory H. Bird; Evripidis Gavathiotis; Michelle L. Stewart; Chelsea Lawrence; Jill K. Fisher; Marina Godes; Kenneth Pitter; Andrew L. Kung; Loren D. Walensky (The Journal of Clinical Investigation, 2012)
Cancer cells subvert the natural balance between cellular life and death, achieving immortality through pathologic enforcement of survival pathways and blockade of cell death mechanisms. Pro-apoptotic BCL-2 family proteins are frequently disarmed in relapsed and refractory cancer through genetic deletion or interaction-based neutralization by overexpressed antiapoptotic proteins, resulting in resistance to chemotherapy and radiation treatments. New pharmacologic strategies are urgently needed to overcome these formidable apoptotic blockades. We harnessed the natural killing activity of BCL-2–interacting mediator of cell death (BIM), which contains one of the most potent BH3 death domains of the BCL-2 protein family, to restore BH3-dependent cell death in resistant hematologic cancers. A hydrocarbon-stapled peptide modeled after the BIM BH3 helix broadly targeted BCL-2 family proteins with high affinity, blocked inhibitory antiapoptotic interactions, directly triggered proapoptotic activity, and induced dose-responsive and BH3 sequence–specific cell death of hematologic cancer cells. The therapeutic potential of stapled BIM BH3 was highlighted by the selective activation of cell death in the aberrant lymphoid infiltrates of mice reconstituted with BIM-deficient bone marrow and in a human AML xenograft model. Thus, we found that broad and multimodal targeting of the BCL-2 family pathway can overcome pathologic barriers to cell death.